1952
DOI: 10.3382/ps.0310571
|View full text |Cite
|
Sign up to set email alerts
|

Effect on Growth of Supplements to Chick Rations Containing Vitamin B12 and Antibiotics

Abstract: Twenty-four New Hampshire pullets assigned at random to 6 sire groups were used to produce a total of 665 chicks. Each chick was injected with 0.6 mg. each of testosterone propionate and stilbestrol dissolved in sesame oil administered in 6 equal injections over a 12-day period. The chicks were then sacrificed and records made on body, comb, and oviduct weights. Analysis of the data revealed that there were significant differences between the sire families and between dam families within sire families with res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1953
1953
1971
1971

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Fuller et al (1952) found, with chicks, that condensed fish solubles, dried whey and liver fractions contained unknown factors, but that these factors were not influenced by the presence or absence of antibiotics. Sunde et al (1952) concluded that fish solubles, torula yeast, meat scraps and condensed homogenized fish contain a factor which stimulates the growth of chicks fed an all-plant ration containing vitamin B12 and an antibiotic. Ringrose and Potter (1952) found fish meal replacement of soybean oil meal to increase growth and feed efficiency, irrespective of Bn.…”
Section: Resultsmentioning
confidence: 99%
“…Fuller et al (1952) found, with chicks, that condensed fish solubles, dried whey and liver fractions contained unknown factors, but that these factors were not influenced by the presence or absence of antibiotics. Sunde et al (1952) concluded that fish solubles, torula yeast, meat scraps and condensed homogenized fish contain a factor which stimulates the growth of chicks fed an all-plant ration containing vitamin B12 and an antibiotic. Ringrose and Potter (1952) found fish meal replacement of soybean oil meal to increase growth and feed efficiency, irrespective of Bn.…”
Section: Resultsmentioning
confidence: 99%
“…Nitekim ilk yapılan ara~tırmaların büyük bir kısmında (I, 5, i 1, 12,13,16,20,21). ribofIavin Je pantoten asid gibi B grubu vitaminlerinin rasyonlarda yetersiz bulunduğu görülmektedir.…”
Section: Introductionunclassified
“…Other work on unidentified growth factors required by the chick and poult (Carlson et al, 1949;Heuser and Norris, 1951;Couch et al, 1952;Fuller et al, 1952;and Sunde et al, 1952) has established the presence of a growth factor or factors in fish meal and fish solubles which has been designated as the "fish factor." The existence of different factors in dried whey and fish products which are additive in the effect on growth has been reported by Couch et al (1952) and Camp et al (1955).…”
mentioning
confidence: 97%